Síntese de copolímeros e pró-fármacos de galactomanana oxidada e derivados aminados por reação de formação de base de schiff - Lima, Laís Ramos Monteiro de (2021)
Dual responsive nanomaterials have been the subject of numerous research in recent years in areas such as in biomaterials and matrix for drug release. Among these systems, the copolymers formed from the thermo-responsive polymer poly- (N-isopropylacrylamide) (PNIPAm) stand out. The present work presents a new route for synthesis of polysaccharide copolymers with PNIPAm via Schiff's base reaction. The reaction used as starting materials the oxidized galactomannan (extracted from Delonix regia seeds) and the amine poly-(N-isopropylacrylamide) (PNIPAm-NH2). Copolymers formed from galactomannan with an oxidation degree of 30% (CP30%-M), as well as the oxidized polysaccharide itself (DRU-Ox30%) were used to form prodrugs with doxorubicin (DOX), an anti-cancer drug. In the synthesis of copolymers, the effects of the degree of oxidation of the main chain (galactomannan) and the molar mass of the side chain (PNIPAm-NH2) were investigated. The starting materials, the copolymers and prodrugs were characterized by spectroscopic and chromatographic techniques. All copolymers showed critical aggregation concentration (CAC) at 25 and 50 °C, with values at 25 °C greater than 50 °C. The thermoinduced self-organization property of copolymers was investigated by dynamic light scattering (DLS). The copolymers showed a transition temperature (LCST) between 34-40 °C. Nanoparticles size at 37 °C ranged from 234 - 365 nm. Copolymers also showed a response to pH variation, with particles at pH 5.0 being greater than pH 7.4, probably due to hydrolysis of the imine bond. The CP30% -M-DOX and DRUOx30% -DOX prodrugs had average particle diameters between 180 and 191 nm and a pH-responsive drug release profile, where a significant increase in the released drug was observed with decreasing pH (pH 5.0). The cytotoxicity of prodrugs was analyzed against tumor (B16F10 and SNB-19) and non-tumor (L929) cells. The prodrugs did not show activity against non-tumor cells; however, they were efficient against B16F10 and SNB-19 cells.